Eclipse - Rash, Andy (2023)
"After hearing about the total solar eclipse happening in two months, a boy makes a plan with his father to go see it. They drive to the perfect campsite, not wanting to miss the couple of minutes when the sun will be completely hidden by the moon. When the moment happens, being together makes it even more special. Based on a trip that author-illustrator Andy Rash took with his son to see the eclipse in August 2017, Eclipse is a heartfelt and playfully illustrated ode to seeking out unique adventures and savoring the most special moments with the people you love. The book features maps of eclipses' paths and scientific back matter about eclipses"--
Color maps on end pages
AGes 4-8
Keywords: Solar eclipses -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Eclipses -- Juvenile fiction; Astronomy -- Juvenile fiction; Solar eclipses -- Juvenile literature; Picture books for children; Realistic fiction